Characterization of Vanadium Ion Uptake in Sulfonated Diels Alder Poly(phenylene) Membranes. Issue 1 (28th November 2015) - Lawton, Jamie S.; Jones, Amanda M.; Tang, Zhijiang; Lindsey, Melanie; Fujimoto, Cy; Zawodzinski, Thomas A.
Abstract : Sulfonated diels alder poly(phenylene) (SDAPP), alternative aromatic hydrocarbon membranes for vanadium redox flow batteries (VRFBs) are characterized using electron paramagnetic resonance (EPR). Membranes soaked in sulfuric acid and vanadyl sulfate are analyzed to determine the membrane environment in which the vanadyl ion (VO 2+ ) diffuses in the membranes. These results are compared to Nafion 117 membranes. In contrast to Nafion, the VO 2+ in SDAPP membranes exists in two different environments. The results of analysis of rotational diffusion determined from fits the EPR spectral lineshapes in comparison with previously reported permeation studies and measurements of partitioning functions reported here suggest that the diffusion pathways in SDAPP are considerably different than in Nafion.